(untitled) (Northern International Medical College Journal, 2018)
Background : Ischemic Heart Disease (IHD) requires long term treatment which poses huge financial burden.It is very difficult for the patients of developing countries to maintain the treatment costs of IHD. Objectives : To estimate the medical treatment cost and to find out the coping ways of that in Ischemic Heart Disease patients.Methods: A descriptive type of cross sectional study was done during January 2014 to December 2014 at medical out-patient department of National Institute of Cardiovascular Disease (NICVD), Dhaka. Data were collected by using a pre-tested, semi-structured Questionnaire. Medical cost was calculated by drug cost, consultation cost, laboratory investigation cost, surgical cost, hospital cost and food cost. Data analysis was performed by using SPSS software version 20. Results : Out of 201 patients, majority (64.7%) were in the age group of 40-59 years. Most (92.54%)of them were male. Majority (56.2%) of the respondents had monthly family income of Tk. 10001-20000. Among all patients 43.8%spent total medical cost was with a range from Tk.50001-180000. 85.71%, 81.8%, 69.9% and 66.71% had coped with families by life style change whose monthly Tk. 20001-50000,Tk. 50001-100000, Tk. 10001-20000, Tk. 5000-10000 respectively. Coping ways in family by compromising treatment cost of other family members was minimum 0.0% within the income group Tk.5000-10000, which was statistically significant (p<0.05). Conclusion : The study concluded that the largest component of medical cost of IHD was the surgical cost which includes coronary angiogram, PTCA and bypass surgery. The patient compensate the burden of medical treatment cost of IHD from family savings, personal income, selling of property, personal loan, donation, health insurance and by Life style change, Reduction of food cost,and reducing social contact. Northern International Medical College Journal Vol.9(1) July 2017: 258-260